Comparing alternative methods for improving the bisection techniques: modified bracketing method and Regula Falsi Algorithm / Nurul Ain Syafika Juperi, Nur Yasmin Hanani Mahdiber and Amylia Natasha Khairul Nizam - Juperi, Nurul Ain Syafika; Mahdiber, Nur Yasmin Hanani; Khairul Nizam, Amylia Natasha (2023)
This study was performed to compare alternative methods for improving the Bisection techniques which are Modified Bracketing Method and Regula Falsi Algorithm. The Bisection method's calculation is quite long and can take a huge amount of time. Besides, it is almost certain that multiple iterations are required to achieve the desired accuracy. This research shows how it is being compared with other methods such as the Modified Bracketing Method and the Regula Falsi Algorithm to analyze which one is the easiest method to implement as well as having the fewest iterations to get close to the root or accuracy. Therefore, the objectives of this study are to apply the Bisection Method, the Modified Bracketing Method and the Regula Falsi Algorithm in solving the various types of nonlinear functions. Next, to identify which algorithm is the most efficient in root-finding by comparing the iteration number among the three methods. Then, some selected test functions are applied into the Bisection Method, Modified Bracketing Method and Regula Falsi Algorithm to decide which is the most practical method. It is observed from the results and comparison of the three methods including Bisection Method, Modified Bracketing Method and Regula Falsi Algorithm that the modification of Bisection method is performing better. Thus, the significance of the result is to identify which approach requires the fewest iterations and takes the least amount of time.